Living sustainably in the city of Prague with Greenie.com : Customer Experience design optimization - Moleš, Jan; Ryška, Tomáš, 1976-; Sieber, Patrik, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
This Master’s thesis uses the design thinking process to create a viable, customer-centric design of a pro-sustainable platform named Greenie.cz. Greenie.cz serves as a gamified guide, assistant and e-commerce site, that helps individuals living in Prague prioritize, adopt and retain pro-environmental behaviours. Seven green consumers dwelling in Prague were interviewed, each of them selected based on the typology of three distinct groups varying in the level of commitment to a sustainable lifestyle. In-depth, semi-structured interviews were thematically analyzed to collect customer pain points, needs and key issues, in which Greenie.cz can provide solutions and create value for its users. The practical part provides nine design elements, that take the form of key features of the platform. A combination of key findings of the primary research and insights gained from the scientific body of the state of the art literature serves as a justification of each design element. Greenie.cz uses the SCB-cube model to provide a structured categorization of pro-environmental behaviours; Prague-centric local focus helps individuals align their lifestyle efforts with the long-term strategy of the city they inhabit; gamification serves as a source of positive motivation; pro-environmental behaviours are listed based on impact and effort level to help individuals prioritize in a meaningful way; the platform uses social presence to leverage the subjective norm and provide social pressure to behave pro-sustainably; the platform eliminates information overload by providing a single source of city-based knowledge on how to conveniently satisfy the needs of a sustainable lifestyle. All features are designed with the Octalysis framework and contemporary literature in mind, to assure a positive online customer experience. In addition, the necessary determinants are considered to fulfil the aim of bridging the green gap.
A proposal of platform monetization options and a feasibility study is provided towards the end of the thesis to showcase the design as a marketable solution.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses